Ultra-processed food intake is associated with increased gastrointestinal tract symptoms and alterations in gut microbiota in patients with systemic sclerosis - Lee, Ju Young; Mahurkar-Joshi, Swapna; Young, Arissa; Labus, Jennifer S.; He, Bofei; Aja, Ezinne; Jacobs, Jonathan P.; Volkmann, Elizabeth R. (Frontiers in Immunology, 2025)
BackgroundAlterations in the gastrointestinal (GI) microbiome (i.e., dysbiosis) are a feature of systemic sclerosis (SSc). Diet is a known modifier of the GI microbiome, and ultra-processed food (UPF) consumption has been associated with adverse changes in GI microbial composition. This study aimed to determine whether UPF consumption affects the GI microbiota and GI symptoms in patients with SSc.MethodsAdult SSc patients provided stool samples and completed both the Diet History Questionnaire II (DHQ-2) and the UCLA Scleroderma Clinical Trial Consortium Gastrointestinal Tract Instrument (GIT 2.0). Shotgun metagenomics were performed using the Illumina NovaSeq 6000 with a target depth of 10 million 150x2 sequences per sample. UPF items (N=54) on the DHQ-2 were identified using the NOVA scale of food classification, and UPF intake was calculated as gram-per-week consumption according to patient reported frequency. General linear models were created to identify differentially abundant species based on UPF consumption and to evaluate the relationship between UPF consumption and GI symptoms as measured by the GIT 2.0. These models adjusted for body mass index (BMI), current proton pump inhibitor (PPI) use, current probiotic use, current or prior immunomodulatory therapy, and presence of small intestinal bacterial overgrowth (SIBO).ResultsOf the 65 total SSc patients included, 84.6% were female. The mean age was 53.83 ± 13.19 years, and the mean BMI was 25.25 ± 4.75. The median UPF consumption was 2395.82 g/week. Increased UPF consumption was significantly associated with increased GI symptoms in our multivariate model (β=0.34; p<0.01). Among 257 species analyzed, 5 bacterial species were significantly associated with UPF consumption in the multivariate models, including Limosilactobacillus fermentum (β=0.32; p<0.01) and Faecalicatena fissicatena (β= -0.36; p-value<0.01), while the abundance of 6 bacterial species was significantly associated with GI symptom severity after adjusting for the aforementioned covariates.ConclusionsSSc patients reporting a higher UPF consumption demonstrated alterations in GI microbial composition as well as increased GI symptoms, even after adjusting for factors known to affect the microbiota of patients with SSc. Future studies are needed to determine whether interventions aimed at lowering UPF consumption may improve GI outcomes for patients with SSc.